STRUCTURE AND SEMANTIC PROPERTIES OF VERBS IN THE ENGLISH AND UZBEK LANGUAGES - Qurbonboyeva Hilola (TADQIQOTLAR, 2025)
A comprehensive examination of the structural and semantic characteristics of verbs in English and Uzbek reveals both striking similarities and notable differences shaped by their respective linguistic typologies. English, belonging to the Indo- European family, and Uzbek, a representative of the Turkic language group, offer unique perspectives on verb formation, grammatical categorization, and semantic representation. This study investigates the morphological patterns, including verb inflection and derivation processes, as well as the systems of tense, aspect, and modality (TAM) in both languages. Additionally, the research analyzes how verbs assign semantic roles such as agent, experiencer, theme, and beneficiary in sentence structures. Through comparative linguistic analysis, key areas of convergence and divergence are identified, especially in relation to verb valency, argument structure, and the expression of modality. The results underscore the complexity and richness of verbal systems in both languages, highlighting the influence of agglutinative versus analytic structures on meaning construction. Insights gained from this study contribute to the broader understanding of cross-linguistic verb semantics and have practical applications in areas such as bilingual education, language acquisition, and the development of accurate translation models between English and Uzbek.